2009
DOI: 10.1128/aac.00722-08
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Ciprofloxacin, Gatifloxacin, Levofloxacin, and Norfloxacin MICs for Fluoroquinolone-Resistant Escherichia coli Clinical Isolates

Abstract: Fluoroquinolones are some of the most prescribed antibiotics in the United States. Previously, we and others showed that the fluoroquinolones exhibit a class effect with regard to the CLSI-established breakpoints for resistance, such that decreased susceptibility (i.e., an increased MIC) to one fluoroquinolone means a simultaneously decreased susceptibility to all. For defined strains, however, clear differences exist in the pharmacodynamic properties of each fluoroquinolone and the extent to which resistance-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…The differences observed seem to be related to the structural differences between the quinolones tested. Both quinolones and fluoroquinolones might be useful for the detection of the low-level resistance caused by these resistance determinants if the right breakpoints are set; so far, however, few data for other quinolone drugs are available (3,19). Nalidixic acid is known to be a very good drug for use for the detection of mutants; however, it would not be useful for the detection of isolates positive for qnr or aac(6Ј)Ib-cr mutations which might be found to have inhibition zones in the susceptible range.…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed seem to be related to the structural differences between the quinolones tested. Both quinolones and fluoroquinolones might be useful for the detection of the low-level resistance caused by these resistance determinants if the right breakpoints are set; so far, however, few data for other quinolone drugs are available (3,19). Nalidixic acid is known to be a very good drug for use for the detection of mutants; however, it would not be useful for the detection of isolates positive for qnr or aac(6Ј)Ib-cr mutations which might be found to have inhibition zones in the susceptible range.…”
Section: Discussionmentioning
confidence: 99%
“…However, these mechanisms do not equally affect the MICs of all fluoroquinolones; in general, ciprofloxacin and norfloxacin MICs are affected by all of these mechanisms, and gatifloxacin and levofloxacin MICs are less affected or are not affected (14,23,26). In a companion study, we found tremendous variation among the MICs of ciprofloxacin, gatifloxacin, levofloxacin, and norfloxacin, such that the four fluoroquinolones were affected to the same extent only in a small subset of isolates (ϳ5%) (4). In addition to the tremendous diversity in MICs of the four tested fluoroquinolones, we recently uncovered clear correlations between fluoroquinolone resistance in Escherichia coli isolates and patient age, patient sex, hospital location, and culture site (3).…”
mentioning
confidence: 93%
“…From our accompanying study of 214 fluoroquinoloneresistant and 27 fluoroquinolone-susceptible E. coli clinical isolates (4), we chose 153 isolates for Western blotting to determine AcrA levels. These isolates represented the full range of ciprofloxacin, gatifloxacin, levofloxacin, and norfloxacin MICs and included isolates ELZ4004, ELZ4032, ELZ4601, and ELZ4686, which had the unprecedented fluoroquinolone MIC relationships (4). For 78 of the isolates with quantified AcrA levels (including the four isolates with unusual resistance phenotypes), we sequenced the topoisomerase QRDRs and screened for the plasmid-located genes aac(6Ј)-Ib-cr and qnrA.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that known genotypic alterations could not explain the fluoroquinolone MICs in ϳ30% of the fluoroquinolone-resistant clinical isolates, suggesting that additional unknown mechanisms exist (2,6). In laboratory strains, the overexpression of mdfA or norE causes 2-to 4-fold increased ciprofloxacin and norfloxacin MICs but has no effect on levofloxacin MICs (17).…”
mentioning
confidence: 99%